2003
DOI: 10.14430/arctic608
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heavy Metals in a Large Mortality Event in Caribou of Northern Alaska

Abstract: ABSTRACT. We measured element concentrations (As, Cd, Cu, Pb, Zn, Fe) and body condition (gross and histologic endpoints) of animals from a caribou (Rangifer tarandus) mortality event that occurred in Alaska, in the area of Point Hope and Cape Thompson (including the Chariot site), in 1995. These were compared to results from hunter-killed caribou from reference sites (Barrow and Teshekpuk Lake, Alaska) and from the area of a mine (Red Dog Mine) to determine whether heavy metals had played a role in the mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Compared to other species of northern Alaska, bowhead whales of this study had similar or lower tissue concentrations of the toxic metal Hg (17,18). The Cd concentrations are similar to those previously reported for bowhead whales (18,27), which accumulate Cd with age in liver, and particularly in kidney (18), similar to other arctic mammals, including both terrestrial and marine species (17,18,32,33,34,35,36,37,38,39). Other reports have addressed potential nutritional and toxic effects of such elemental concentrations in bowhead whales and domestic animals (32,18).…”
Section: Discussionsupporting
confidence: 84%
“…Compared to other species of northern Alaska, bowhead whales of this study had similar or lower tissue concentrations of the toxic metal Hg (17,18). The Cd concentrations are similar to those previously reported for bowhead whales (18,27), which accumulate Cd with age in liver, and particularly in kidney (18), similar to other arctic mammals, including both terrestrial and marine species (17,18,32,33,34,35,36,37,38,39). Other reports have addressed potential nutritional and toxic effects of such elemental concentrations in bowhead whales and domestic animals (32,18).…”
Section: Discussionsupporting
confidence: 84%
“…Higher concentrations of As near RDM are probably not related to mining activities. Although studies have found high levels of As in stream sediments [28] and caribou tissues [8,29], the concentration of As in ore from RDM has been shown to be no higher than that observed within local soil samples [7]. Hence, higher concentrations of As may occur naturally within the RDM region.…”
Section: Discussionmentioning
confidence: 99%
“…Dust from ore removal and transportation has been identified as a source of heavy metal contamination [2,3]. Based upon these findings, numerous assessments have quantified the risks of contamination for people using local resources for food (e.g., [4][5][6][7][8]). Although studies of marine sediments identified elevated concentrations of barium, cadmium, chromium, copper, silver, strontium, and zinc near Red Dog Mine port site, no contaminants exceeded the screening standards used to assess human health (see description of screening standards [7]).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies with lead authors from local and territorial governments has increased over time, but these studies remain a small proportion of the papers published in Arctic, representing fewer than 7% of papers published between 2008 and 2010. Within our sample, examples include education research from the late 1990s (Stenton andRigby 1995, Norton andKassam 1997) and wildlife management studies from the last decade (O'Hara et al 2003, Person et al 2007, which actively engaged communities in every aspect of the research process. It is not surprising that papers with lead authors from local and territorial governments tend toward Mode 2 in heterogeneity, especially because they often involved authors and funding from other levels of government and/or universities.…”
Section: Researcher Organizationmentioning
confidence: 99%